CACAT FISIK PADA FIGUR MANUSIA DALAM KARYA SENI GRAFIS (RELIEF PRINT) PHYSICAL DISABILITY IN HUMAN FIGUR GRAPHIC ARTWORK IN RELIEF PRINT - Iswandi Nur, Drs, Irwan, M.Sn., Yofita sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2016)
The physical condition of humans who do not comply with expectations usually interfere with its movement. In general, for the physically disabled is difficult to achieve, both in education and other fields, and this often creates a psychological problem, because with the physical shortcomings with physical disabilities will find themselves helpless and useless in becoming members of the public. However, there are also some people with physical disabilities who have high motivation to excel. The emergence of this idea came from the writer's observation of the physically disabled who accomplished so an inspiration in the creation of works of this thesis. The purpose in making this thesis is to visualize Physical Disabilities In Human Form in relief print, graphic arts.Methods of process in making this work is done through perujutan ideas of art with several steps: Preparation (preparation), the search for ideas, perujutan concepts and ideas, relationship concept, completion (finishing).These works are created through various processes and experiences in the life of the author himself. As for the work that the author created was entitled: 1. Runners, 2. Ballet, 3. Painting, Dancer 4. Umbrella, 5. Play Guitar, Piano 6. Main, 7. Motivator, 8. Javelin 9. Marathon, 10. Drawing.Keywords: Disabled, Graphic Arts, Print Relief.